Asymmetric development of drainage networks as a factor for the recognition of neotectonic block rotation. The case of Stournarorema and Belesitsas basins (Fokida prefecture, Greece) - ΦΟΥΝΤΟΥΛΗΣ Ι.; ΦΟΥΜΕΛΗΣ Μ. (Bulletin of the Geological Society of Greece, 2001)
The aim of the present study is to ditect large scale neotectonic deformation in the wider area of Eratini (South Sterea region), by examining its drainage network, the planation surfaces and the structural contour map of the contact between Bardousia and Pindos geotectonic units. In particular we examined the asymmetry of Stournarorema and Belesitsas (tributary of Mornos river) basins. The main interest of this attempt was to reveal systematic orientation of the Tranverse Topographic Symmetry Vector ’T’ as will as its geographic distribution. Thus we estimated the above asymmetry factor for the 3rd order streams of both basins and taking in consideration the influence of the tectonic structure and the lithology of the area to the estimated asymmetry values, we suggest a possible counterbalancing rotation of these basins along a horizontal axis of NE-SW direction